Optimizing Mobile Deployments - Schwartz, Ariel; Bhavsar, Mohini; Cutrell, Ed; Donner, Jonathan; Densmore, Melissa (2014)
Mobile devices are increasingly powerful and flexible tools for grassroots work. This document offers guidelines for thinking about your deployment, drawing attention to the latent project features that can influence the use of a device you issue for community level or frontline social service work.